Using the andersen healthcare utilization model to assess willingness to screen for prep in pharmacy-based settings among cisgender sexually minoritized men: results from the 2020 american men's internet survey - Daniel I. Alohan; Gabrielle Evans; Travis Sanchez; Kristin R.V. Harrington; Alvan Quamina; Henry N. Young; Natalie D. Crawford (BMC, 2024)
Abstract Background Pre-exposure prophylaxis (PrEP) to prevent HIV is severely underutilized among sexually minoritized men (SMM). Inequitable access to PrEP-prescribing facilities and providers is a critical barrier to PrEP uptake among SMM. Integrating HIV prevention services, such as PrEP screening, into pharmacy-based settings is a viable solution to addressing HIV inequities in the US. We aimed to examine willingness to obtain PrEP screening in a pharmacy and its associated correlates, leveraging Andersen's Healthcare Utilization Model (AHUM), among a national sample of SMM in the U.S. Methods Data from the 2020 American Men's Internet Survey, an annual online survey among SMM, were analyzed. Drawing on AHUM-related constructs, we used a modified stepwise Poisson regression with robust variance estimates to examine differences in willingness to screen for PrEP in a pharmacy. Estimated prevalence ratios (PR) were calculated with 95% confidence intervals (CI95%). Results Out of 10,816 men, most (76%) were willing to screen for PrEP in a pharmacy. Participants were more willing to screen for PrEP in a pharmacy if they (1) had a general willingness to use PrEP (PR = 1.52; CI95% =1.45, 1.59); (2) felt comfortable speaking with pharmacy staff about PrEP (PR = 2.71; CI95% =2.47, 2.98); and (3) had HIV-related concerns (PR = 1.04; CI95% =1.02, 1.06). There were no observed differences in men's willingness to screen for PrEP in a pharmacy by race/ethnicity, education level, annual household income, nor insurance status. Conclusions Strategically offering PrEP screening in pharmacies could mitigate access-related barriers to HIV prevention services among SMM, particularly across various sociodemographic domains. Importantly, this approach has vitally important implications for addressing broader inequities in HIV prevention. Future studies should examine strategies to successfully integrate PrEP screenings in pharmacies among diverse populations, especially among those at elevated risk for HIV.